Comparative biology of bagworm larvae (Metisa plana) fed on oil palm (Elaeis guineensis) and malabar melastome (Melastoma malabathricum) - ANGGRAINI, ERISE; ISTIQOMAH, HAWARYAH; IRSAN, CHANDRA; HERLINDA, SITI; MUSLIM, A.; SUWANDI, SUWANDI (Smujo International, 2025)
Abstract. Anggraini E, Istiqomah H, Irsan C, Herlinda S, Muslim A, Suwandi S. 2025. Comparative biology of bagworm larvae (Metisa plana) fed on oil palm (Elaeis guineensis) and malabar melastome (Melastoma malabathricum). Asian J Agric 9: 472-481. Metisa plana Walker, 1883 (Lepidoptera: Psychidae) is a significant defoliator in oil palm plantations, and the weed Melastoma malabathricum L. (malabar melastome) is believed to act as an alternative host, potentially maintaining pest numbers. This study assessed the comparative biology of M. plana larvae raised individually on oil palm and malabar melastome leaves in a laboratory setting. Recently emerged larvae (n?=?10 per treatment) were observed for leaf area consumption, larval bag form, developmental time, and survival rates. The results indicated that larvae consuming malabar melastome had a substantially greater leaf area consumption during instars 1-3 (up to 11.44?±?0.96?cm²) compared to those fed on oil palm (8.91?±?0.58?cm²; p?<?0.05), with the differences becoming non-significant from the 4th instar forward. The total duration of larval development was roughly 109 days on Malabar melastome and 103 days on oil palm, with no statistically significant difference (p > 0.05), while survival rates above 80% on both hosts. The length of larval bags exhibited substantial variation in the early instars (p < 0.01), but remained comparable in subsequent stages, and pupal weight was not assessed. The findings affirm that M. malabathricum serves as an appropriate alternate host for M. plana, underscoring the necessity for integrated weed management to avert malabar melastome from functioning as a reservoir, thereby enhancing the efficacy of pest management measures in oil palm ecosystems.